2023
DOI: 10.1161/circulationaha.123.065251
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Biomarkers, Canagliflozin, and Outcomes in Diabetic Kidney Disease: The CREDENCE Trial

James L. Januzzi,
Reza Mohebi,
Yuxi Liu
et al.

Abstract: BACKGROUND: People with type 2 diabetes and albuminuria are at an elevated risk for cardiac and renal events. The optimal biomarkers to aid disease prediction and to understand the benefits of sodium-glucose cotransporter-2 inhibition remain unclear. METHODS: Among 2627 study participants in the CREDENCE trial (Canagliflozin and Renal Events in Diabetes With Established Nephropathy Clinical Evaluation), concentrations of NT-proBNP (N-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…In this study, 1 The study showed that baseline concentrations of each biomarker were strongly predictive of cardiac and renal outcomes. When the biomarkers were analysed together in a multimarker panel, individuals with high and moderate risk scores showed a higher risk for these outcome compared with those with low risk scores.…”
mentioning
confidence: 78%
“…In this study, 1 The study showed that baseline concentrations of each biomarker were strongly predictive of cardiac and renal outcomes. When the biomarkers were analysed together in a multimarker panel, individuals with high and moderate risk scores showed a higher risk for these outcome compared with those with low risk scores.…”
mentioning
confidence: 78%
“…Neben der antihypertensiven Wirkung hat diese Medikamentenklasse zudem eine antiproteinurische und eine harnsäuresenkende Wirkung, sodass SGLT-2i zu den Standardmedikamenten neben ACEi/ARB bei CKD-Patienten gehören. Die Reduktion von kardiovaskulären und renalen Endpunkten dieser Wirkstoffklasse wurde eindrucksvoll in mehreren Studien gezeigt (CREDENCE [31], DAPA-CKD [32], EMPA-KIDNEY [33]). In der Post-hoc-Analyse der DELIVER-Studie, in die Patienten mit Herzinsuffizienz mit erhaltener Ejektionsfraktion (HFpEF) eingeschlossen waren, erwies sich, dass weniger Patienten mit therapieresistenter Hypertonie unter Dapagliflozin das primäre Outcome erreichen (kardiovaskulärer Tod und Verschlechterung der Herzinsuffizienz).…”
Section: Leitlinieunclassified
“…The non-hypoglycemic effects of SGLT2i have been extensively studied and documented in several publications, both in original research and review articles [32][33][34]. In this comprehensive review, we aimed to focus specifically on cardiovascular and renal biomarkers, as a way to provide quantitative insights into biological processes, disease progression and treatment response, and summarize the most recent knowledge on the changes induced by SGLT2i treatment in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%